EVALUATION OF THE PROSPECTS OF EDUCATIONAL AVAILABILITY IN LITHUANIAN DISTRICTS IN THE CONTEXT OF THE SOCIAL DEVELOPMENT OF THE COUNTRY’S TERRITORIES - Luobikienė, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Scientists, national politicians and specialists from Lithuania and other countries identified the main determinants of the social development of the territories of Lithuania, the problems of the society, which have been influenced by this development, and possible trends of change. Although the social development of Lithuanian territories is determined by a "bundle" of social problems, the focus of the article is on those that may affect the availability of education in the most sparsely populated districts of Lithuania. The aim of this article is to reveal the prospects of education availability in the most sparsely populated areas of Lithuania in the context of the social development of the country's territories. The main problem question related to this is what prospects for the availability of education in the most sparsely populated areas of the country presuppose the social development of Lithuania's territories. In order to achieve the aim of the article, the design of the research was based on the theoretical analysis of the problem raised and a secondary analysis of the data in the field. The main findings of the research reflect the situation in the field of study, and the conclusions of the research drawn on the basis of them provide an assessment of the prospects of education accessibility in the most sparsely populated areas of Lithuania.